Propagación vegetativa en banano (Musa paradisiaca) con el micriirganismo beneficio (Trichoderma harzianum) VS convencional - Astudillo Intriago, Enrique Egberto (2012)
This work was performed at the Hacienda "Maria Luisa" owned by Mr. Arturo Andrade, located at Km 35 road Quevedo - Santo Domingo, Canton Valencia, province of Los Rios. The location is 1 ° 3 '18''south latitude and 79 ° 25' 24'' west longitude at an altitude of 73 meters. Raised the overall objective: To evaluate the vegetative propagation of banana (Musa paradisiaca) with beneficial microorganism Trichoderma harzianum vs conventional and specific: a) determine the agronomic performance during vegetative propagation of banana using Trichoderma and ryzup b) Establish treatment with the best cost / benefit ratio. Subject to the assumptions: a) The use of beneficial microorganism Trichoderma harzianum produces a higher number of roots of banana (Musa paradisiaca) and b) Treatment with Trichoderma harzianum, will present a better cost / benefit ratio. We used a randomized block design with three treatments and six replicates to determine differences between treatment means will be used multiple range test of Tukey at 0.05% probability. The use of Trichoderma promoted greater plant height at 90 days of study, or 8 cm to 23 cm Witness and about treatment with gibberellic acid. The number of leaves and leaf length at 90 days of Trichoderma and Witness, were superior to gibberellic acid treatment, which made no leaves. The use of ryzup (gibberellic acid) inhibited the development of leaves within 90 days of study, possibly because of an imbalance caused auxins and cytokinins, delaying the issuance of the leaves. Dose with Trichoderma plants, led to increased root length and number of roots during 90 days of investigation. The use of Trichoderma caused a greater weight of roots at 30, 60 and 90 days. The use of Trichoderma raised the average cost / plant at a value of $ 1.58, seven cents more expensive than using the control treatment (Furadan).